The alternative serotonin transporter promoter P2 impacts gene function in females with irritable bowel syndrome. Issue 16 (24th June 2021) - Mohr, Sandra; Fritz, Nikola; Hammer, Christian; Martínez, Cristina; Berens, Sabrina; Schmitteckert, Stefanie; Wahl, Verena; Schmidt, Malin; Houghton, Lesley A.; Goebel‐Stengel, Miriam; Kabisch, Maria; Götze, Dorothea; et al.
Abstract: Irritable bowel syndrome (IBS) is a gut‐brain disorder in which symptoms are shaped by serotonin acting centrally and peripherally. The serotonin transporter gene SLC6A4 has been implicated in IBS pathophysiology, but the underlying genetic mechanisms remain unclear. We sequenced the alternative P2 promoter driving intestinal SLC6A4 expression and identified single nucleotide polymorphisms (SNPs) that were associated with IBS in a discovery sample. Identified SNPs built different haplotypes, and the tagging SNP rs2020938 seems to associate with constipation‐predominant IBS (IBS‐C) in females. rs2020938 validation was performed in 1978 additional IBS patients and 6, 038 controls from eight countries. Meta‐analysis on data from 2, 175 IBS patients and 6, 128 controls confirmed the association with female IBS‐C. Expression analyses revealed that the P2 promoter drives SLC6A4 expression primarily in the small intestine. Gene reporter assays showed a functional impact of SNPs in the P2 region. In silico analysis of the polymorphic promoter indicated differential expression regulation. Further follow‐up revealed that the major allele of the tagging SNP rs2020938 correlates with differential SLC6A4 expression in the jejunum and with stool consistency, indicating functional relevance. Our data consolidate rs2020938 as a functional SNP associated with IBS‐C risk in females, underlining the relevance of SLC6A4 in IBS pathogenesis.